Factores del mercadeo ecológico en las microempresas artesanales del estado Zulia, Venezuela - Baralt Rincón, Andreina (Scripta Mundi, 2023)
Ecological marketing contributes, on one hand, to sustainable development, meeting social needs in the implementation of production processes that are respectful of the environment, up to the final consumption of the product; on the other hand, it enables business performance by generating clean quality products, and in turn, a good image for its consumers. For this reason, this article’s main purpose is to analyze the factors of ecological marketing in artisanal microenterprises in the state of Zulia, Venezuela. The methodology used is descriptive with a field design, through the application of two questionnaires; one made to the representatives of the Zulian artisan groups, attached to the Department of Culture of the University of Zulia, and another, to the consumers found in the artisan markets of the region. The results show that the artisans of the Zulia region take into account the factors of ecological marketing; such as, the quality of the products made, the preference of consumers to acquire artisan products and their form of commercial image.